Perceived versus actual knowledge of alcohol and halal food among food technology undergraduate students in a Malaysian university - Ahmad, Anis Najiha; Yang, Tajul A; Wan Abdullah, Wan Nadiah (Emerald Group Publishing Limited, 2015)
Purpose – The purpose of this study is to evaluate the perceived knowledge of the general concept of halal food and actual knowledge of halal food principles with emphasis on alcohol (alcoholic drinks and ethanol). Design/methodology/approach – A cross-sectional descriptive survey, using quantitative research methods, was utilized. A self-administered survey was distributed to 188 undergraduate students of the food technology programme at Universiti Sains Malaysia, and a total of 114 responses were obtained. Findings – Results indicate that respondents believed that they have above average competence regarding the concept, sources, ingredients, processing and the overall production of halal foods (score: 3.75-4.18). In addition, all of the 114 respondents also agreed that alcoholic drinks are fundamentally prohibited in Islam. However, the survey also revealed that the respondents were less certain about the application of alcohol in halal food production. Respondents’ actual knowledge on these issues was low to average. Research limitations/implications – This study is limited by its cross-sectional nature. In addition, the research was only conducted on undergraduate-level students of the food technology programme, and therefore, results derived might not be generalized to the other segments of the population. The overall uncertainty and misconception about the application of alcohol in halal food highlights the need to improve the knowledge of these undergraduate students to more than a mere theory of the concepts of halal and haram. Originality/value – No previous study has been conducted to explore the issue pertaining to alcohol in halal food, and this paper categorically strives to fill this gap.